Hadith #2138 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Isa bin Hammad bin Muslim, Zaghba عيسى بن حماد بن مسلم أبو موسى زغبة; Marthad bin 'Abdullah al-Yazni مرثد بن عبد الله اليزني; Uqba bin 'Amir al-Juhayni; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
A’ishah wife of the Prophet (ﷺ) reported “When the Apostle of Allaah(ﷺ) intended to go on a journey he cast lots amongst his wives and the one who was chosen by lot went on it with him. He divided his time, day and night (equally) for each of his wives except that Saudah daughter of Zam’ah gave her day to A’ishah.
Grade: Sahih

Hadith #2153 - Sunan Abi Dawud - Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; al-Q'qa' bin Hkym al-Knany القعقاع بن حكيم الكناني المدني; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
Abu Hurairah reported the Prophet (ﷺ) as saying “ Every child of Adam has his share in adultery. He then narrated the rest of the tradition. This version goes “And the hands commit adultery; their adultery is catching; and the legs commit adultery; their adultery is walking; and the mouth commits adultery – its adultery is kissing.”
Grade: Sahih

Hadith #2179 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Nafie' نافع مولى ابن عمر; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
‘Abd Allah bin Umar said that he divorced his wife while she was menstruating during the time of the Apostle of Allaah(ﷺ). So ‘Umar bin Al Khattab asked the Apostle of Allaah(ﷺ) about this matter. The Apostle of Allaah(ﷺ) said “Order him, he must take her back and keep her back till she is purified, then has another menstrual period and is purified. Thereafter if he desires he may divorce her before having intercourse with her, for that is the period of waiting which Allaah the Glori
Grade: Sahih

Hadith #2267 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) entered upon me. The version of Musaddad and Ibn as-Sarh has: one day looking pleased”. The version of Uthman has: “The lines of his forehead were realised.” He said: O Aisha, are you not surprised to hear that Mujazziz al-Mudlaji saw that Zayd and Usamah had a rug over them concerning their heads and letting their feet appear. He said: These feet are related. Abu Dawud: Usamah was black and Zaid was white.
Grade: Sahih

Hadith #2384 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Bukayr bin 'Abdullah bin al-Ashj بكير بن عبد الله بن الأشج; Isa bin Hammad bin Muslim, Zaghba عيسى بن حماد بن مسلم أبو موسى زغبة; Jabir ibn 'Abdullah (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to kiss me when he was fasting and when I was fasting.
Grade: Sahih

Hadith #2412 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Isa bin Hammad bin Muslim, Zaghba عيسى بن حماد بن مسلم أبو موسى زغبة; Marthad bin 'Abdullah al-Yazni مرثد بن عبد الله اليزني; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
Ja’far ibn Jubayr said: I accompanied AbuBusrah al-Ghifari, a Companion of the Messenger of Allah (ﷺ), in a boat proceeding from al-Fustat (Cairo) during Ramadan. He was lifted (to the boat), then his meal was brought to him. The narrator Ja’far said in his version: He did not go beyond the houses (of the city) but he called for the dining sheet. He said (to me): Come near. I said: Do you not see the houses? AbuBusrah said: Do you detest the sunnah (practice) of the Messenger of Allah (ﷺ
Grade: Sahih

Hadith #2422 - Sunan Abi Dawud - Abdul Malik bin Shu'aib bin al-Laith عبد الملك بن شعيب بن الليث بن سعد; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; al-Laith bin Sa'd الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم (Sunan Abi Dawud)
That the Prophet (ﷺ) entered upon her on Friday while she was fasting. He asked: Did you fast yesterday ? She said: No. He again asked: Do you intend to fast tomorrow ? She said: No. He said: So break your fast.
Grade: Sahih

Hadith #2461 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Laith bin Sa'd الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Aqil bin Khalid bin 'Aqil عقيل بن خالد بن عقيل الأيلي; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
When one of you is invited (to a meal), and he is fasting, he should say that he is fasting.
Grade: Sahih

Hadith #2467 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Aisha bint Abi Bakr; al-Laith bin Sa'd الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) observed I’tikaf, he would put his head near me, and I would comb it. and he entered the house only to fulfill human needs (i.e. to urinate or to relieve himself).
Grade: Sahih

Hadith #2486 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Laith bin Sa'd الليث بن سعد; Ali bin 'Ayyash علي بن عياش; Haywat bin Sharih bin Safwan حيوة بن شريح بن صفوان التجيبي (Sunan Abi Dawud)
A man said: Messenger of Allah, allow tourism for me. The Prophet (ﷺ) said: The tourism of my people is striving in the path of Allah, the Exalted.
Grade: Hasan

Hadith #2525 - Sunan Abi Dawud - Abdul Malik bin Shu'aib bin al-Laith عبد الملك بن شعيب بن الليث بن سعد; Abdullah bin 'Amr bin al-'Aas; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; al-Laith bin Sa'd الليث بن سعد; Hajjaj bin Muhammad al-Musaysi حجاج بن محمد المصيصي الأعور; Haywat bin Sharih bin Safwan حيوة بن شريح بن صفوان التجيبي (Sunan Abi Dawud)
AbuAyyub heard the Messenger of Allah (ﷺ) say: Capitals will be conquered at your hands, and you will have to raise companies in large armies. A man will be unwilling to join a company, so he will escape from his people and go round the tribes offering himself to them, saying: Whose place may I take in such and such expedition? Whose place may I take in such and such expedition? Beware: That man is a hireling to the last drop of his blood.
Grade: Da'if

Hadith #2564 - Sunan Abi Dawud - Abdullah bin Zryr عبد الله بن زرير; al-Laith bin Sa'd الليث بن سعد; Ali ibn Abi Talib; Marthad bin 'Abdullah al-Yazni مرثد بن عبد الله اليزني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
Jabir reported the Prophet (ﷺ) as saying when an ass which had been branded on its face passed him. Did it not reach you that I cursed him who branded the animals on their faces or struck them on their faces. So he prohibited it.
Grade: Sahih

Hadith #2585 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
The tradition mentioned above has also been narrated by Anas bin Malik through a different chain of narrators. He mentioned similar words. Abu Dawud said “the strongest of these traditions is the one of Sa’id bin Abu Al Hasan. The rest are weak.
Grade: Sahih

Hadith #2614 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; ibn Umar; Nafie' نافع مولى ابن عمر; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
The Prophet (ﷺ) said: Go in Allah’s name, trusting in Allah, and adhering to the religion of Allah’s Apostle. Do not kill a decrepit old man, or a young infant, or a child, or a woman; do not be dishonest about booty, but collect your spoils, do right and act well, for Allah loves those who do well.
Grade: Da'if

Hadith #2643 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; al-Miqdad ibn al-Aswad; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ata'a bin Yazid al-Laithi al-Junda'i عطاء بن يزيد الليثي الجندعي; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Ubaidullah bin 'Ady bin al-Khayyar (Sunan Abi Dawud)
Usamah bin Zaid said “The Messenger of Allah (ﷺ) sent us with a detachment to Al Huruqat. They learnt about us and fled away. But we found a man, when we attacked him he uttered “There is no god but Allaah, still we struck him till we killed him.” When I mentioned it to the Prophet (ﷺ) he said “Who will save you from “There is no god but Allaah” on the Day of Judgment? I said “Messenger of Allah (ﷺ), he uttered it for the fear of the weapon.” He said “Did you tear his hea
Grade: Sahih

Hadith #2667 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; ibn Umar; Nafie' نافع مولى ابن عمر; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Yazid bin Khalid bin Yazid يزيد بن خالد بن يزيد (Sunan Abi Dawud)
Al-Hayyaj ibn Imran ibn Husayn reported that a slave of Imran ran away. He took a vow to Allah that if he overpowers him, he will cut off his head. He then sent me (to Samurah ibn Jundub) to ask him about this question for him. I came to Samurah ibn Jundub and asked him. He said: The Messenger of Allah (ﷺ) used to exhort us to give alms (sadaqah) and forbid us to mutilate (a slain). I then came to Imran ibn Husayn and asked him. He said: The Messenger of Allah (ﷺ) used to exhort us to give a
Grade: Sahih

Hadith #2673 - Sunan Abi Dawud - Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Bukayr bin 'Abdullah bin al-Ashj بكير بن عبد الله بن الأشج; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث; Yazid bin Khalid bin Yazid يزيد بن خالد بن يزيد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) appointed him commander over a detachment. He said: I went out along with it. He (the Prophet) said: If you find so-and-so, burn him with the fire. I then turned away, and he called me. So I returned to him, and he said: If you find so-and-so, kill him, and do not burn him, for no one punishes with fire except the Lord of the fire.
Grade: Sahih

Hadith #2678 - Sunan Abi Dawud - Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Isa bin Hammad bin Muslim, Zaghba عيسى بن حماد بن مسلم أبو موسى زغبة; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) sent Abdullah ibn Ghalib al-Laythi along with a detachment and I was also with them. He ordered them to attach Banu al-Mulawwih from all sides at al-Kadid. So we went out and when we reached al-Kadid we met al-Harith ibn al-Barsa al-Laythi, and seized him. He said: I came with the intention of embracing Islam, and I came out to go to the Messenger of Allah (ﷺ). We said: If you are a Muslim, there is no harm if we keep you in chains for a day and night; and if you
Grade: Da'if

Hadith #2692 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; al-Miswar bin Makhrama bin Nawfal; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Aqil bin Khalid bin 'Aqil عقيل بن خالد بن عقيل الأيلي; Marwan bin Mua'wiya al-Fazari مروان بن معاوية الفزاري; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
When the people of Mecca sent about ransoming their prisoners Zaynab sent some property to ransom Abul’As, sending among it a necklace of hers which Khadijah had had, and (which she) had given to her when she married Abul’As. When the Messenger of Allah (ﷺ) saw it, he felt great tenderness about it and said: If you consider that you should free her prisoner for her and return to her what belongs to her, (it will be well). They said: Yes. The Messenger of Allah (ﷺ) made an agreement with
Grade: Hasan

Hadith #2745 - Sunan Abi Dawud - Abdul Malik bin Shu'aib bin al-Laith عبد الملك بن شعيب بن الليث بن سعد; al-Laith bin Sa'd الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Aqil bin Khalid bin 'Aqil عقيل بن خالد بن عقيل الأيلي; ibn Umar; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Shu'aib bin al-Laith bin Sa'd شعيب بن الليث بن سعد (Sunan Abi Dawud)
‘Abd Allaah (bin ‘Umar) said “The Apostle of Allaah(ﷺ) sent us along with a detachment. The share of each was twelve Camels. The Apostle of Allaah(ﷺ) gave each one of us a Camel as a reward. Abu Dawud said “Burd bin Sinan narrated a similar tradition from Nafi’ as narrated by ‘Ubaid Allaah. Ayyub also narrated from Nafi’ a similar tradition, but his version goes “We were rewarded one Camel each. He did not mention the Prophet (ﷺ).
Grade: Sahih

Hadith #2878 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; al-Laith bin Sa'd الليث بن سعد; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan Abi Dawud)
‘Umar got some land in Khaibar, and when to the Prophet (ﷺ) and said: I have acquired land in Khaibar which I consider to be more valuable than any I have acquired ; so what do you command me to do with it ? He replied: If you wish, you may make the property as inalienable possession, and give its produce as sadaqah (charity). So ‘Umar gave it as a sadaqah declaring that the property must not be sold, given away, or inherited : (and gave its produce as sadaqah to be devoted) to poor, relat
Grade: Sahih

Hadith #2943 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Basr bin Sa'id al-Madni بسر بن سعيد المدني العابد; Bukayr bin 'Abdullah bin al-Ashj بكير بن عبد الله بن الأشج; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: When we appoint someone to an administrative post and provide him with an allowance, anything he takes beyond that is unfaithful dealing.
Grade: Sahih

Hadith #2967 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Aqil bin Khalid bin 'Aqil عقيل بن خالد بن عقيل الأيلي; Urwa ibn al-Zubayr عروة بن الزبير; Yazid bin Khalid bin Yazid يزيد بن خالد بن يزيد (Sunan Abi Dawud)
Malik ibn Aws al-Hadthan said: One of the arguments put forward by Umar was that he said that the Messenger of Allah (ﷺ) received three things exclusively to himself: Banu an-Nadir, Khaybar and Fadak. The Banu an-Nadir property was kept wholly for his emergent needs, Fadak for travellers, and Khaybar was divided by the Messenger of Allah (ﷺ) into three sections: two for Muslims, and one as a contribution for his family. If anything remained after making the contribution of his family, he div
Grade: Hasan

Hadith #3002 - Sunan Abi Dawud - Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: If you gain a victory over the men of Jews, kill them. So Muhayyisah jumped over Shubaybah, a man of the Jewish merchants. He had close relations with them. He then killed him. At that time Huwayyisah (brother of Muhayyisah) had not embraced Islam. He was older than Muhayyisah. When he killed him, Huwayyisah beat him and said: O enemy of Allah, I swear by Allah, you have a good deal of fat in your belly from his property.
Grade: Da'if

Hadith #3138 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; al-Laith bin Sa'd الليث بن سعد; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) combined two persons from among the martyrs of Uhud (in one garment), and said: Which of the two has learnt the Qur’an more ? When one of them was pointed to him, he advanced him in the grave, saying: I shall be witness to all these (martyrs) on the Day of Judgement. He then ordered them to be buried without being washed.
Grade: Sahih

Hadith #3222 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Marthad bin 'Abdullah al-Yazni مرثد بن عبد الله اليزني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Uqba bin 'Amir al-Juhayni; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
The Prophet (ﷺ) said: There is no slaughtering (at the grave) in Islam. ‘Abd al-Razzaq said: They used to slaughter cows or sheep at grave.
Grade: Sahih

Hadith #3351 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Fadala bin 'Ubaid bin Naqid; Hnsh bin 'Abdullah حنش بن عبد الله ويقال; Khalid bin Abi 'Imran خالد بن أبي عمران; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Yazid al-Humayri سعيد بن يزيد الحميري القتباني (Sunan Abi Dawud)
The Prophet (ﷺ) was brought a necklace in which there were gold and pearls. (The narrators AbuBakr and (Ahmad) Ibn Mani’ said: The pearls were set with gold in it, and a man bought it for nine or seven dinars.) The Prophet (ﷺ) said: (It must not be sold) till the contents are considered separately. The narrator said: He returned it till the contents were considered separately. The narrator Ibn Asa said: By this I intended trade. Abu Dawud said: The word hijarah (stone) was recorded in his
Grade: Sahih

Hadith #3352 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Fadala bin 'Ubaid bin Naqid; Hnsh bin 'Abdullah حنش بن عبد الله ويقال; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
At the battle of Khaibar I bought a necklace in which there were gold and pearls for twelve dinars. I separated them and found that its worth was more than twelve dinars. So I mentioned that to the Prophet (ﷺ) who said: It must not be sold till the contents are considered separately.
Grade: Sahih

Hadith #3391 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; al-Laith bin Sa'd الليث بن سعد; Hnzlh bin Qays bin 'Amr حنظلة بن قيس بن عمرو; Ibrahim bin Musa al-Razi al-Fara' إبراهيم بن موسى الرازي الفراء; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Rafi' bin Khadij bin Rafi' (Sunan Abi Dawud)
We used to lease land for what grew by the streamlets and for what was watered from them. The Messenger of Allah (ﷺ) forbade us to do that, and commanded us to lease if for gold or silver.
Grade: Hasan

Hadith #3408 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; ibn Umar; Nafie' نافع مولى ابن عمر; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) made an agreement with the people of Khaibar to work and cultivate in return for half of the fruits or produce.
Grade: Sahih

Hadith #3455 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Laith bin Sa'd الليث بن سعد; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan Abi Dawud)
“Or one of them tells the other: “Exercise the right.”
Grade: Sahih

Hadith #3468 - Sunan Abi Dawud - Abu Sa'id al-Khudri; al-Laith bin Sa'd الليث بن سعد; Ayyad bin 'Abdullah bin Sa'd عياض بن عبد الله بن سعد بن أبي سرح; Bukayr bin 'Abdullah bin al-Ashj بكير بن عبد الله بن الأشج; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone pays in advance he must not transfer it to someone else before he receives it.
Grade: Da'if

Hadith #3485 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Ata' bin Abi Rabah عطاء بن أبي رباح; Jabir ibn 'Abdullah; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: Allah forbade wine and the price paid for it, and forbade dead meat and the price paid for it, and forbade swine and the price paid for it.
Grade: Sahih

Hadith #3634 - Sunan Abi Dawud - Abu Da'ud أبو داود السجستاني الأزدي; al-Laith bin Sa'd الليث بن سعد; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
When one of you asks permission for inserting a wooden peg in his wall, he should not prevent him. So they (the people) lowered down their heads. Then he (Abu Hurairah) said: What is the matter ? I am seeing you are neglecting (to hear this tradition), I shall spread it among you. Abu Dawud said:This is the tradition of Ibn Abi Khalaf is more perfect.
Grade: Sahih

Hadith #3636 - Sunan Abi Dawud - Abdullah ibn al-Zubayr; al-Laith bin Sa'd الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
Give it to him and you can have such and such, mentioning something with which he tried to please him, but he refused. He then said: You are a nuisance. The Messenger of Allah (ﷺ) then said to the Ansari: Go and uproot his palm-trees.
Grade: Da'if

Hadith #3702 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Ata' bin Abi Rabah عطاء بن أبي رباح; Jabir ibn 'Abdullah; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
Dates were steeped for the Messenger of Allah (ﷺ) in a skin, but when they could not find a skin, they were steeped for him in a small stone vessel.
Grade: Sahih

Hadith #3751 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Marthad bin 'Abdullah al-Yazni مرثد بن عبد الله اليزني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Uqba bin 'Amir al-Juhayni; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
The Prophet (ﷺ) said: If any Muslim is a guest of people and is given nothing, it is the duty of every Muslim to help him to the extent of taking for him from their crop and property for the entertainment of one night.
Grade: Hasan

Hadith #3761 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Jabir ibn 'Abdullah; Khalid bin Yazid خالد بن يزيد الجمحي الإسكندراني; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
I read in the Torah that the blessing of food consists in ablution before it. So I mentioned it to the Prophet (ﷺ). He said: The blessing of food consists in ablution before it and ablution after it. Sufyan disapproved of performing ablution before taking food. Abu Dawud said: It is weak.
Grade: Da'if

Hadith #3891 - Sunan Abi Dawud - Abu al-Darda; al-Laith bin Sa'd الليث بن سعد; Fadala bin 'Ubaid bin Naqid; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Yazid bin Khalid bin Yazid يزيد بن خالد بن يزيد (Sunan Abi Dawud)
I had a pain which was about to destroy me. So the Prophet (ﷺ) said : Wipe it with your right hand seven times and say : “I seek refuge in the dominance of Allah, and His might from the evil of what I find.” Then I did it. Allah removed (the pain) that I had, and I kept on suggesting it to my family and to others.
Grade: Sahih

Hadith #3928 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Aisha bint Abi Bakr; al-Laith bin Sa'd الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said to us: If one of you has a slave, and he enters into an agreement to purchase his freedom, and can pay the full price, she must veil herself from him.
Grade: Hasan

Hadith #3961 - Sunan Abi Dawud - Abdullah bin lahya'a bin 'Uqba عبد الله بن لهيعة بن عقبة الحضرمي; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Laith bin Sa'd الليث بن سعد; Bukayr bin 'Abdullah bin al-Ashj بكير بن عبد الله بن الأشج; ibn Umar; Nafie' نافع مولى ابن عمر; Ubaidullah bin Abi Ja'far عبيد الله بن أبي جعفر المصري (Sunan Abi Dawud)
A man emancipated six slaved at the time of his death and he had no other property. The Prophet (ﷺ) was informed about it. He cast lots among them, emancipated two and retained four in slavery.
Grade: Sahih

Hadith #4027 - Sunan Abi Dawud - Abdullah bin 'Ubaidullah b. Abi Mulayka عبد الله بن عبيد الله بن أبي مليكة; al-Laith bin Sa'd الليث بن سعد; al-Miswar bin Makhrama bin Nawfal; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Yazid bin Khalid bin Yazid يزيد بن خالد بن يزيد (Sunan Abi Dawud)
The sleeve of the shirt of the Messenger of Allah (ﷺ) came to the wrist.
Grade: Hasan

Hadith #4056 - Sunan Abi Dawud - Abdullah bin Zryr عبد الله بن زرير; al-Laith bin Sa'd الليث بن سعد; Ali ibn Abi Talib; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) gave license to ‘Abd al-Rahman b. ‘Awf and al-Zubair b. al-‘Awwam to wear silk shirts during a journey because of an itch which they had.
Grade: Sahih

Hadith #4104 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
Asma, daughter of AbuBakr, entered upon the Messenger of Allah (ﷺ) wearing thin clothes. The Messenger of Allah (ﷺ) turned his attention from her. He said: O Asma’, when a woman reaches the age of menstruation, it does not suit her that she displays her parts of body except this and this, and he pointed to his face and hands. Abu Dawud said: This is a mursal tradition (i.e. the narrator who transmitted it from ‘Aishah is missing) Khalid b. Duraik did not see ‘Aishah.
Grade: Sahih

Hadith #4154 - Sunan Abi Dawud - Abu Talha Ansari; al-Laith bin Sa'd الليث بن سعد; Basr bin Sa'id al-Madni بسر بن سعيد المدني العابد; Bukayr bin 'Abdullah bin al-Ashj بكير بن عبد الله بن الأشج; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Zayd bin Khalid al-Juhni (Sunan Abi Dawud)
I said: Mother, he has told me that the Prophet (ﷺ) has said: He also said the words ; Sa’id b. yasir client of Banu al-Najjar.
Grade: Sahih

Hadith #4262 - Sunan Abi Dawud - Abdur Rahman bin Jbyr عبد الرحمن بن جبير المصري; al-Laith bin Sa'd الليث بن سعد; al-Miqdad ibn al-Aswad; Hajjaj bin Muhammad al-Musaysi حجاج بن محمد المصيصي الأعور; Mu'awiya bin Salah bin Hadayr معاوية بن صالح بن حدير (Sunan Abi Dawud)
The Prophet (ﷺ) said: Before you there will be commotions like pieces of a dark night in which a man will be a believer in the morning and an infidel in the evening. He who sits during them will be better than he who gets up, and he who gets up during them is better than he who walks, and he who walks during them is better than he who runs. They (the people) said: What do you order us to do? He replied: Keep to your houses.
Grade: Sahih

Hadith #4263 - Sunan Abi Dawud - Abdul Malik bin Shu'aib bin al-Laith عبد الملك بن شعيب بن الليث بن سعد; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Khalid bin Abi 'Imran خالد بن أبي عمران; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan Abi Dawud)
I swear by Allah, I heard the Messenger of Allah (ﷺ) say: The happy man is he who avoids dissensions: happy is the man who avoids dissensions; happy is the man who avoids dissensions: but how fine is the man who is afflicted and shows endurance.
Grade: Sahih

Hadith #4264 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Laith bin Sa'd الليث بن سعد; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Tawus bin Kaysan طاوس (Sunan Abi Dawud)
The Prophet (ﷺ) said: There will be civil strife (fitnah) which will render people deaf, dumb and blind regarding what is right. Those who contemplate it will be drawn by it, and giving rein to the tongue during it will be like smiting with the sword.
Grade: Da'if

Hadith #4368 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu al-Zanad أبو الزناد; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; al-Laith bin Sa'd الليث بن سعد (Sunan Abi Dawud)
He then forbade disfiguring. This version does not mention the words “ from opposite sides” . This tradition has been narrated by Shu’bah from Qatadah and Salam bin Miskin from Thabit on the authority of Anas. They did not mention the words “from opposite side”. I did not find these words “their hands and feet were cut off from opposite sides”. In any version except in the version of Hammad bin Salamah.
Grade: Sahih

Hadith #4371 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Laith bin Sa'd الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Urwa ibn al-Zubayr عروة بن الزبير; Yazid bin Khalid bin Yazid يزيد بن خالد بن يزيد (Sunan Abi Dawud)
This happened before the prescribed punishments(hudud) were revealed, meaning the tradition of Anas.
Grade: Sahih

Hadith #4388 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Laith bin Sa'd الليث بن سعد; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan Abi Dawud)
Muhammad ibn Yahya ibn Hibban said: A slave stole a plant of a palm-tree from the orchard of a man and planted it in the orchard of his master. The owner of the plant went out in search of the plant and he found it. He solicited help against the slave from Marwan ibn al-Hakam who was the Governor of Medina at that time. Marwan confined the slave and intended to cut off his hand. The slave’s master went to Rafi’ ibn Khadij and asked him about it. He told him that he had heard the Messenger of
Grade: Sahih

Hadith #4394 - Sunan Abi Dawud - Abu Salah Maula 'Uthman أبو صالح مولى عثمان; Aisha bint Abi Bakr; al-Laith bin Sa'd الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Urwa ibn al-Zubayr عروة بن الزبير; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
I was sleeping in the mosque on a cloak mine whose price was thirty dirhams. A man came and pinched it away from me. The man was seized and brought to the Messenger of Allah (ﷺ). He ordered that his hand should be cut off. I came to him and said: Do you cut off only for thirty dirhams ? I sell it to him and make the payment of its price a loan ? He said: Why did you not do so before bringing him to me ? Abu Dawud said: Za’idah has also transmitted it from Simak from Ju’ayd ibn Hujayr. He s
Grade: Sahih

Hadith #4489 - Sunan Abi Dawud - Abdur Rahman bin Jabir bin 'Abdullah عبد الرحمن بن جابر بن عبد الله; Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; al-Laith bin Sa'd الليث بن سعد; Bukayr bin 'Abdullah bin al-Ashj بكير بن عبد الله بن الأشج; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
I saw the Messenger of Allah (ﷺ) on the morning of the conquest of Mecca when I was a young boy. He was walking among the people, seeking the camp of Khalid ibn al-Walid. A man who had drunk wine was brought (before him) and he ordered them (to beat him). So they beat him with what they had in their hands. Some struck him with whips, some with sticks and some with sandals. The Messenger of Allah (ﷺ) threw some dust on his face. When a man who had drunk wine was brought before AbuBakr, he ask
Grade: Hasan

Hadith #4575 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Abi Dawud)
One of the two women of Hudhayl killed the other, Each of them had husband and sons. The Messenger of Allah (ﷺ) fixed the blood-wit for the slain woman to be paid by the woman’s relatives on the father’s side. He declared her husband and the child innocent. The relatives of the woman who killed said: We shall inherit from her. The Messenger of Allah (ﷺ) said: No, her sons and her husband should inherit from her.
Grade: Sahih

Hadith #4609 - Sunan Abi Dawud - Abu Idrees al-Khulani أبو إدريس الخولاني; al-Laith bin Sa'd الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Aqil bin Khalid bin 'Aqil عقيل بن خالد بن عقيل الأيلي; Yazid bin Khalid bin Yazid يزيد بن خالد بن يزيد (Sunan Abi Dawud)
If anyone summons other to follow right guidance, his reward will be equivalent to that of the people who follow him, without their rewards being diminished in any respect on that account; and if anyone summons others to follow error the sin of which sins being diminished in any respect on that account.
Grade: Sahih

Hadith #4854 - Sunan Abi Dawud - Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) would sit and we would also sit around him. If he got up intending to return, he would take off his sandals or something he was wearing, and his Companions recognising his purpose (that he would return) would stay where they were.
Grade: Da'if

Hadith #4860 - Sunan Abi Dawud - Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Aqil bin Khalid bin 'Aqil عقيل بن خالد بن عقيل الأيلي; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Abi Dawud)
The Prophet (ﷺ) said: None of my Companions must tell me anything about anyone, for I like to come out to you with no ill-feelings.
Grade: Da'if

Hadith #4863 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
when the Prophet(ﷺ) walked, it looked as if he bent forwards.
Grade: Sahih

Hadith #4882 - Sunan Abi Dawud - Abu Talha Ansari; al-Laith bin Sa'd الليث بن سعد; Ishaq bin al-Sabah al-Kundi إسحاق بن الصباح الكندي الأشعثي; Isma'il bin Basheer إسماعيل بن بشير مولى بني مغالة; Jabir ibn 'Abdullah; Sa'id bin Abi Maryam سعيد بن أبي مريم (Sunan Abi Dawud)
Everything of a Muslim is sacred to a Muslim : his property, honour and blood. It is enough evil for any man to despise his brother Muslim.
Grade: Sahih

Hadith #4890 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Ibrahim bin Nshyt إبراهيم بن نشيط; Ka'b bin 'Alqama bin Ka'b كعب بن علقمة بن كعب; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Sa'id bin Abi Maryam سعيد بن أبي مريم (Sunan Abi Dawud)
Zayd ibn Wahb said: A man was brought to Ibn Mas’ud. He was told: This is so and so, and wine was dropping from his beard. Abdullah thereupon said: We have been prohibited to seek out (faults). If anything becomes manifest to us, we shall seize it.
Grade: Sahih

Hadith #4891 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Aqil bin Khalid bin 'Aqil عقيل بن خالد بن عقيل الأيلي; ibn Umar; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب (Sunan Abi Dawud)
The Prophet (ﷺ) said: He who sees something which should be kept hidden and conceals it will be like one who has brought to life a girl buried alive.
Grade: Hasan

Hadith #4894 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Isa bin Hammad bin Muslim, Zaghba عيسى بن حماد بن مسلم أبو موسى زغبة; Sa'id bin Abi Sa'id; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Abi Dawud)
when two men abuse one another, what they say is laid to the charge of the one who began it, so long as the one who is wronged does not go over the score.
Grade: Sahih

Hadith #4951 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Ibn Ishaq محمد بن إسحاق بن يسار‎; Isa bin Hammad bin Muslim, Zaghba عيسى بن حماد بن مسلم أبو موسى زغبة; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
Have you some dates? I said : Yes. I then gave him some dates which he put in his mouth, chewed them, opened his mouth and them in it. The baby began to lick them. The prophet (May peace be upon him) said: ANSAR’s favourite (fruit) is dates. And he gave him the name of ‘Abd al-Rahman.
Grade: Sahih

Hadith #4972 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Ja'far bin Rabi'ya bin Shrhbyl جعفر بن ربيعة بن شرحبيل; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي (Sunan Abi Dawud)
I heard the Messenger of Allah (May peace be upon him) say: it is a bad riding-beast for a man (to say) za’ama (they asserted). Abu DAwud said : This Abu ‘Abd Allah is Hudhaifah.
Grade: Sahih

Hadith #4989 - Sunan Abi Dawud - Abu 'Amir al-Huzani أبو عامر الهوزني; al-Laith bin Sa'd الليث بن سعد; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
Avoid falsehood, for falsehood leads to wickedness, and wickedness to hell; and if a man continues to speak falsehood and makes falsehood his object, he will be recorded in Allah’s presence as a great liar. And adhere to truth, for truth leads to good deeds, and good deeds lead to paradise. If a man continues to speak the truth and makes truth his object, he will be recorded in Allah’s presence as eminently truthful.
Grade: Sahih

Hadith #5020 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Yazid bin Khalid bin Yazid يزيد بن خالد بن يزيد (Sunan Abi Dawud)
The Prophet (ﷺ) said: The vision flutters over a man as long as it is not interpreted , but when it is interpreted, it settles. And I think he said: Tell it only to one who loves (i.e. friend) or one who has judgment.
Grade: Sahih

Hadith #5033 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Isa bin Hammad bin Muslim, Zaghba عيسى بن حماد بن مسلم أبو موسى زغبة; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
When one of you sneezes, he should say: “Praise be to Allah in every circumstance,” and his brother or his companion should say: “May Allah have mercy on you!” And he should then reply: “May Allah guide you and set right your affairs.”
Grade: Sahih

Hadith #5074 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin Sa'id bin Sakhar أحمد بن سعيد بن صخر; al-Laith bin Sa'd الليث بن سعد; al-Rabi' bin Sulaiman الربيع بن سليمان; ibn Abbas; Sa'id bin Basahyr al-Azdi سعيد بن بشير الأزدي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) never failed to utter these supplications in the evening and in the morning: O Allah, I ask Thee for security in this world and in the Hereafter: O Allah! I ask Thee for forgiveness and security in my religion and my worldly affairs, in my family and my property; O Allah! conceal my fault or faults (according to Uthman’s version), and keep me safe from the things which I fear; O Allah! guard me in front of me and behind me, on my right hand and on my left, and fro
Grade: Sahih

Hadith #5100 - Sunan Abi Dawud - Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Ja'far bin Rabi'ya bin Shrhbyl جعفر بن ربيعة بن شرحبيل; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
Because it has recently been with its Lord.
Grade: Sahih

Hadith #5102 - Sunan Abi Dawud - Abdullah ibn 'Amr bin Haram; al-Laith bin Sa'd الليث بن سعد; Jabir ibn 'Abdullah; Khalid bin Yazid خالد بن يزيد الجمحي الإسكندراني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Abi Hilal سعيد بن أبي هلال الليثي; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
when you hear the cocks crowing, ask Allah for some of His grace, for they have seen as angel; but when you hear an ass braying, seek refuge in Allah from the devil, for it has seen the devil.
Grade: Sahih

Hadith #5141 - Sunan Abi Dawud - Abdullah bin Dinar عبد الله بن دينار العدوي; Ahmed bin Manay' أحمد بن منيع; al-Laith bin Sa'd الليث بن سعد; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; ibn Umar (Sunan Abi Dawud)
A man’s reviling of his parents is one of the grave sins. He was asked : Messenger of Allah! How does a man revile his parents? He replied: He reviles the father of a man who then reviles his father, and he reviles a man’s mother and he reviles his.
Grade: Sahih

Hadith #5192 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Laith bin Sa'd الليث بن سعد; Marthad bin 'Abdullah al-Yazni مرثد بن عبد الله اليزني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
Ikrimah said: A group of people from Iraq said: Ibn Abbas, what is your opinion about the verse in which we have been commanded whatever we have been commanded, but no one acts upon it? The word of Allah, Most High, reads: “O ye who believe! Let those whom your right hands possess, and the (children) among you, who have not come of age, ask your permission (before) they enter your presence on three occasions: before morning prayer, while you are undressing for the noonday heat, and after late-
Grade: Hasan

Hadith #5243 - Sunan Abi Dawud - Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Isa bin Hammad bin Muslim, Zaghba عيسى بن حماد بن مسلم أبو موسى زغبة; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
The Prophet (ﷺ) said: In the morning alms are due from every bone in man’s fingers and toes. Salutation to everyone he meets is alms; enjoining good is alms; forbidding what is disreputable is alms; removing what is harmful from the road is alms; having sexual intercourse with his wife is alms. The people asked: He fulfils his desire, Messenger of Allah; is it alms? He replied: Tell me if he fulfilled his desire where he had no right, would he commit a sin ? He then said: Two rak’ahs which
Grade: Sahih

Hadith #5255 - Sunan Abi Dawud - al-Laith bin Sa'd الليث بن سعد; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني (Sunan Abi Dawud)
After that I saw it again in his house.
Grade: Hasan